Analysis of properties of reversible steganography methods - Zimnicki, Piotr; Kozieł, Grzegorz (Journal of Computer Sciences Institute, 2018)
Steganography is a science that deals with hiding information in other information, and it’s becoming increasingly popular with rapid growth of Internet utilization. Reversible steganography methods allow lossless recovery of not only the message, but the cover image as well. Different methods have different characteristics, and thus different applications. This paper aims to deepen the understanding of selected reversible methods, their strong and weak point, through both theoretical and practical analysis. The comparison of chosen methods is presented in the paper.